Saudi Teachers' Perceptions of In‐Service Education and Training Addressing Attention‐Deficit/Hyperactivity Disorder. Issue 2 (20th April 2020) - Abed, Mohaned G.; Shackelford, Todd K.
Abstract: Worldwide, 3.0–7.0 percent of school‐aged children meet criteria for a diagnosis of Attention‐Deficit/Hyperactivity Disorder (ADHD). In Saudi Arabia, ADHD appears to be more prevalent than the worldwide average, with estimates of 12.6–16.7 percent. Unfortunately, there is a relative dearth of research addressing ADHD and related training programs in Saudi Arabia. We investigated perceptions of teachers in Saudi elementary schools regarding current In‐Service Education and Training (INSET) programs addressing students diagnosed with ADHD. We interviewed 40 teachers (15 women and 25 men) from public elementary schools in Jeddah, Saudi Arabia. The findings highlight the need to develop INSET programs specifically addressing best practices for managing and educating students diagnosed with ADHD.